Predictive direct torque control using a cascade asymmetric multilevel converter - Verne, Santiago Andrés (2016)
A Direct Torque Control scheme which regulates the flux and the electromagnetictorque of an induction motor (IM) is presented in this paper. A Cascade Asymmetric Multilevel Converter (CAMC) drives the IM in 7-level mode using a new voltage value for the flying capacitors. An integrated control scheme based on the Finite-Control- Set Model Predictive Control (FCS-MPC) approach undertakes the solution as a unique multi-objective control problem. The algorithm directly selects theswitching states according to a rule of optimization and avoiding the use of modulators and nested controllers.